ANALYZE MEMORY II:: ORGANIZING, FORGETTEN AND MEMORY MODELS - Yurita Tiro; Neviyarni (Literasi Nusantara, 2021)
Organizing in memory, about analyzing memory II: which is a process carried out to compile a memory so that it is easier to remember compilation activities that have a purpose to form structures in memory that have ways and procedures for arranging memory models and reducing the problem of forgetting to the problem individual day-to-day. Forgetting, is something that causes a lot of people to easily fret about what individuals think, forgetting can hinder effectiveness in the planning and learning process. Forgetting is usually caused by several main causes due to the length of time information is stored in memory but not used or not repeated so that, when new information appears, there is forgetting because it doesn't repeat what was previously stored. Analyzing memory II provides insight into how organization, forgetting and memory models make it easy for individuals to continue to be able to analyze their memories.Keywords: Organizing, Forgotten, Memory Model